2017
DOI: 10.1007/s00586-017-5165-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hypertension on the occurrence of postoperative spinal epidural hematoma following single level microscopic posterior lumbar decompression surgery in a single institute

Abstract: Our results demonstrate that the pre-operative high blood pressure value was the most essential risk factor for PSEH, although there was no difference in the preoperative hypertension treatment. Consequently, management of pre-operative blood pressure and post-operative drainage will be crucial for preventing PSEH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 19 publications
1
39
0
Order By: Relevance
“…The relationship between blood pressure and hematoma was widely studied in previous studies [4,5,16,17]. According to our study, although univariate analysis revealed that SBP at different time point except for intraoperative were signi cant higher in delayed onset PSEH group, further multiple logistic regression analysis revealed patients with high postoperative SBP had a 1.10-fold increased risk to develop hematoma.…”
Section: Risk Factorsmentioning
confidence: 45%
See 1 more Smart Citation
“…The relationship between blood pressure and hematoma was widely studied in previous studies [4,5,16,17]. According to our study, although univariate analysis revealed that SBP at different time point except for intraoperative were signi cant higher in delayed onset PSEH group, further multiple logistic regression analysis revealed patients with high postoperative SBP had a 1.10-fold increased risk to develop hematoma.…”
Section: Risk Factorsmentioning
confidence: 45%
“…Two possible explanations may account for it as follow: First, patients usually present an elevation in blood pressure after surgery because of wound pain, but the self-regulation mechanisms can rapidly adjust the vessels size to decrease the blood pressure. However, these poorly managed or undiscovered hypertension patients, owing to hardening vessels, self-regulation mechanism failed to regulate the vessel size and the high blood pressure may lead to hemorrhage again after surgery [16,18]; Second, previous studies have reported the positive relationship between whole blood viscosity (WBV) and hypertension [19][20][21]. The high postoperative SBP may result in high WBV that could cause blood clots and block the drainage tube.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Regardless of the location of postoperative hematoma, the symptoms are usually bilateral, although in our study 12 patients experienced unilateral neurological deficits ( Table 3). Cases of patients with lumbar postoperative hematoma who developed unilateral neurological symptoms have been reported 6,16) . In patients with cervical and thoracic postoperative hematoma, hemiplegia is rare.…”
Section: Discussionmentioning
confidence: 99%
“…Our search for an explanation found that Fujita et al 61 in 2018 identified that hypertension, multilevel surgery, and lordosis less than 25° were considered risk factors. On the other hand, Fujiwara et al 62 found in 2017 that hypertension and lack of debit in surgical drainage were also risk factors. Our patient had hypertension, a lordosis of 23°, and was without drainage, maybe for that reason the patient was at more risk to develop this complication.…”
Section: Discussionmentioning
confidence: 99%